2022
DOI: 10.4251/wjgo.v14.i7.1239
|View full text |Cite
|
Sign up to set email alerts
|

KIFC3 promotes proliferation, migration and invasion of esophageal squamous cell carcinoma cells by activating EMT and β-catenin signaling

Abstract: BACKGROUND Esophageal squamous cell carcinoma (ESCC) is one of the most common malignancies. A total of 45 kinesin superfamily proteins (KIFs) have been identified in humans, among which several family members have demonstrated varied functions in tumor pathobiology via different mechanisms, including regulation of cell cycle progression and metastasis. KIFC3 has microtubule motor activity and is involved in cancer cell invasion and migration, as well as survival. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“… 9 Kinesin Family member C3 (KIFC3), a kinesin superfamily protein, was upregulated in ESCC tissues and associated with poor prognosis in patients with ESCC, and mechanistic studies indicated that KIFC3 promoted proliferation, migration, and invasion of ESCC via β-catenin signaling and EMT. 10 YAP activation driven by C12orf59, a novel cancer-related factor prominently higher in both tumor tissues and most ESCC cell lines, contributes to the EMT of ESCC, and thereby, combined treatment of C12orf59, and YAP inhibitors could be developed as a therapeutic strategy for metastatic ESCC. 11 Furthermore, a recent study revealed that neuron-specific gene family member 1 may amplify the ERK signaling pathway to promote ESCC cell EMT.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Kinesin Family member C3 (KIFC3), a kinesin superfamily protein, was upregulated in ESCC tissues and associated with poor prognosis in patients with ESCC, and mechanistic studies indicated that KIFC3 promoted proliferation, migration, and invasion of ESCC via β-catenin signaling and EMT. 10 YAP activation driven by C12orf59, a novel cancer-related factor prominently higher in both tumor tissues and most ESCC cell lines, contributes to the EMT of ESCC, and thereby, combined treatment of C12orf59, and YAP inhibitors could be developed as a therapeutic strategy for metastatic ESCC. 11 Furthermore, a recent study revealed that neuron-specific gene family member 1 may amplify the ERK signaling pathway to promote ESCC cell EMT.…”
Section: Introductionmentioning
confidence: 99%